THE ROLE OF SUSTAINABLE TOURISM IN THE RESTORATION OF THE ARAL SEA REGION - Solijonov Sunnatilla (TADQIQOTLAR, 2026)
Abstract This paper discusses the role of sustainable tourism in the recovery and development of the Aral Sea region. The study examines the environmental and socio- economic consequences of the Aral Sea crisis and analyzes how tourism may contribute to local economic activity, environmental awareness, and regional cooperation. Special attention is given to eco-tourism, educational tourism, and community-based tourism initiatives. The paper also considers the role of students and young specialists in promoting sustainability and regional development in Central Asia. Although tourism cannot solve the environmental problems of the region, it may become an important supporting factor for long-term recovery and international attention.